THE TRANSLATION OF METAPHORS FROM ENGLISH INTO TOBA BATAK IN OLD TESTAMENT BIBLE - Jon Piter Situmorang; Ayu Rista Sihotang (Muse: Jurnal of Art, 2025)
This article deals with the translation of metaphors from English to Toba Batak. The data were from the Old Testament Bible. The article aims at exploring how metaphors are translated and adapted into the Toba Batak language. The researchers categorized them into four types anthropomorphic image metaphors, animal image metaphors. Abstract metaphors, and synesthesia imagery metaphors. The research uses Parera’s theory of metaphor as the analytical framework. The results show that most metaphors are translated metaphorically, yet there are cases where the translation deviates to fit the cultural context of the Toba Batak language. The findings highlight the linguistic and cultural challenges in translating metaphors across languages with different cultural references and religious interpretations. This research contributes to a better understanding of the complexities involved in metaphor translation, especially in religious texts.